Antibiofilm and Antivirulence Properties of 6-Polyaminosteroid Derivatives against Antibiotic-Resistant Bacteria - Delphine Vergoz; Hung Le; Benoit Bernay; Annick Schaumann; Magalie Barreau; Flore Nilly; Florie Desriac; Ali Tahrioui; Jean-Christophe Giard; Olivier Lesouhaitier; Sylvie Chevalier; Jean Michel Brunel; et al. (MDPI AG, 2023)
The emergence of multi-drug resistant pathogens is a major public health problem, leading us to rethink and innovate our bacterial control strategies. Here, we explore the antibiofilm and antivirulence activities of nineteen 6-polyaminosterol derivatives (squalamine-based), presenting a modulation of their polyamine side chain on four major pathogens, i.e., carbapenem-resistant A. baumannii (CRAB) and P. aeruginosa (CRPA), methicillin-resistant S. aureus (MRSA), and vancomycin-resistant E. faecium (VRE) strains. We screened the effect of these derivatives on biofilm formation and eradication. Derivatives 4e (for CRAB, VRE, and MRSA) and 4f (for all the strains) were the most potent ones and displayed activities as good as those of conventional antibiotics. We also identified 11 compounds able to decrease by more than 40% the production of pyocyanin, a major virulence factor of P. aeruginosa. We demonstrated that 4f treatment acts against bacterial infections in Galleria mellonella and significantly prolonged larvae survival (from 50% to 80%) after 24 h of CRAB, VRE, and MRSA infections. As shown by proteomic studies, 4f triggered distinct cellular responses depending on the bacterial species but essentially linked to cell envelope. Its interesting antibiofilm and antivirulence properties make it a promising a candidate for use in therapeutics.